Citation Analysis of Sports Medicine Research, 1981-1996 Productivity, Impact and Influence of Nations, Institutions and Researchers - Garfield, E. (1997)
Thirty years of detailed studies have demonstrated the validity of citation analysis. Citation analyses correlate well with peer judgments of significance. Thus, citation analysis should generally bring to light which papers, people, institutions, nations, and journals have contributed in greatest measure to the advance of research in a specific field. That's the approach we've taken with sports medicine. There is a fundamental distinction that must be made in a multi-disciplinary field like sports medicine. On the one hand, there is what we can call the literature of sports medicine. Then there is the literature of interest to sports medicine researchers. The first part of my presentation utilizes the literature of sports medicine -- narrowly defined by the top 53 sports medicine journals. The second part of my talk concerns the additional scientific journals that sports researchers depend upon from fields like physiology, nutrition, cardiology and orthopedics. Citation analysis is controversial but its relevance is rarely disputed when it draws on large aggregations of data. In this talk, I will provide a global macro-perspective by nation, institution, or journal. Then we'll take a microview of the most-published and most-cited authors. At an even more specific level, we'll look at long-term, high-impact papers and then more recent hot papers.